2018
DOI: 10.1038/s41598-018-24701-8
|View full text |Cite
|
Sign up to set email alerts
|

A compendium of long non-coding RNAs transcriptional fingerprint in multiple myeloma

Abstract: Multiple myeloma (MM) is a clonal proliferation of bone marrow plasma cells characterized by highly heterogeneous genetic background and clinical course, whose pathogenesis remains largely unknown. Long ncRNAs (lncRNAs) are a large class of non-protein-coding RNA, involved in many physiological cellular and genomic processes as well as in carcinogenesis and tumor evolution. Although still in its infancy, the role of lncRNAs in MM is progressively expanding. Besides studies on selected candidates, lncRNAs expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…The significance of this lncRNA-protein coding region homology remains unclear. XXbac-B444P24.14 was identified in a screen for differentially regulated lncRNAs in multiple myeloma (Ronchetti et al, 2018). As with many of the annotated lncRNAs currently curated in the human genome, future studies will need to ascertain the functional contributions of those haploinsufficient due to 22q11.2del and assess the consequences of this on the clinical phenotypes.…”
Section: Emerging Noncoding Rnas and Their Potential Roles In 22q112delmentioning
confidence: 99%
“…The significance of this lncRNA-protein coding region homology remains unclear. XXbac-B444P24.14 was identified in a screen for differentially regulated lncRNAs in multiple myeloma (Ronchetti et al, 2018). As with many of the annotated lncRNAs currently curated in the human genome, future studies will need to ascertain the functional contributions of those haploinsufficient due to 22q11.2del and assess the consequences of this on the clinical phenotypes.…”
Section: Emerging Noncoding Rnas and Their Potential Roles In 22q112delmentioning
confidence: 99%
“…No differences could be detected even when CLL cells were compared separately with either normal naïve or memory B cells, which are considered closer to CLL cells (Supplementary Figure S2) [14,16]. CLL cells expressed significantly more NEAT1 than those of the other hematological neoplasias with the exception of MM cells, which are known to express high levels of this lncRNA (Figure 1a, left panel) [17]. Next, we verified the correlation between the two NEAT1 isoforms in all the populations analyzed and, with the exception of the small group of B-lymphoma cell lines, we found that NEAT1_2 expression levels positively correlated with those of NEAT1_1 ( Figure 1b).…”
Section: Ofmentioning
confidence: 99%
“…Interestingly they found 21 lncRNAs, whose expression was deregulated proceeding toward the more aggressive stages of PC dyscrasias (PCL), suggesting a possible role in the disease progression [148]. In a follow up study, RNA-seq was used to evaluate lncRNA expression in 30 MM patients leading to the identification of 391 dysregulated lncRNAs [149]. The authors also provided a comprehensive catalogue of lncRNAs specifically associated with the main MM molecular subgroups and genetic alterations [149].…”
Section: Lncrnasmentioning
confidence: 99%
“…In a follow up study, RNA-seq was used to evaluate lncRNA expression in 30 MM patients leading to the identification of 391 dysregulated lncRNAs [149]. The authors also provided a comprehensive catalogue of lncRNAs specifically associated with the main MM molecular subgroups and genetic alterations [149]. Samur et al described the lncRNA landscape in MM cells by RNA-seq on MM PCs from 308 newly-diagnosed and uniformly treated patients enrolled to DFCI/IFM 2009 clinical study and on normal PCs from 16 HDs [150].…”
Section: Lncrnasmentioning
confidence: 99%